Forced Displacement : Moving from Managing Risk to Facilitating Opportunity - Lakhani, Sadaf (World Bank, Washington, DC, 2013)
Displacement is most commonly perceived as a situation of crisis; a time in which risks to the displaced and to host communities need to be mitigated and managed. However, if managed well, displacement can also bring new opportunities for the displaced and host communities to improve their lives. This paper looks at the predominant reasons why displacement is viewed and assisted by the aid community as a humanitarian issue, rather than as a phenomenon for which development thinking and development solutions are to be applied. Policies and program approaches that facilitate the realization of opportunities are also explored. Specifically, the authors examine the obstacles associated with the shift away from perceiving displacement through a humanitarian lens, to responding to displacement as a development challenge. The paper asserts that the second point of view can open up opportunities to significantly improve the life of millions around the world.